2014
DOI: 10.3390/s140713210
|View full text |Cite
|
Sign up to set email alerts
|

Small Infrared Target Detection by Region-Adaptive Clutter Rejection for Sea-Based Infrared Search and Track

Abstract: This paper presents a region-adaptive clutter rejection method for small target detection in sea-based infrared search and track. In the real world, clutter normally generates many false detections that impede the deployment of such detection systems. Incoming targets (missiles, boats, etc.) can be located in the sky, horizon and sea regions, which have different types of clutters, such as clouds, a horizontal line and sea-glint. The characteristics of regional clutter were analyzed after the geometrical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…If the background level increases, the threshold increases automatically, which leads to constant false alarms. Recently, Kim and Lee proposed a hysteresis thresholdbased constant false alarm rate (H-CFAR) detector [23]. As shown in Figure 4(a), the original CFAR (O-CFAR) detector probes all the pixels above the noise level [24].…”
Section: Background Of the Small Infrared Target Detection Methodsmentioning
confidence: 99%
“…If the background level increases, the threshold increases automatically, which leads to constant false alarms. Recently, Kim and Lee proposed a hysteresis thresholdbased constant false alarm rate (H-CFAR) detector [23]. As shown in Figure 4(a), the original CFAR (O-CFAR) detector probes all the pixels above the noise level [24].…”
Section: Background Of the Small Infrared Target Detection Methodsmentioning
confidence: 99%
“…Most studies [11,23,25] indicated that the background is the comparatively dark sea surface and the ship targets might be relatively local brighter regions. According to these above-mentioned methods and theories, the accurate bright ship target detection algorithm for TIR image is established.…”
Section: Proposed Bright Ship Target Detection In Tir Imagesmentioning
confidence: 99%
“…However, in real cases, dark ship targets whose infrared radiation is lower than surroundings also exist in the backlighting infrared images. To detect dark infrared ship targets, Equations (4), (9), (8), and (10) in the Steps 1-5 of Algorithm 1 can be replaced by Equations (5), (12), (11), and (13), respectively, to compute normalized IFSM of dark ship image. Meanwhile, Equations (5), (12), (11), and (14) in the Steps 6-10 of Algorithm 1 can be replaced by Equations (4), (9), (8), and (15), respectively, to compute normalized BCSM of dark ship image.…”
Section: Proposed Small Ship Target Detection In Tir Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [9] analyzed the characteristics of regional cluster and removed the false detection by means of spatial attribute-based classifications, the heterogeneous background removal filter, and temporal consistency filter. Motivated by the background classification and coastal region detection, Kim et al [10] proposed a novel scene-dependent small target detection strategy involving the relationships between the geometric horizon and the image horizon. By classifying the infrared background types and detecting the littoral regions in omni-directional images, coastal regions can be detected by fusing the region map and curve map.…”
Section: Introductionmentioning
confidence: 99%